Industrial-scale valorization of fine recycled aggregates in cement raw meal: Towards sustainable mixtures. (15th August 2022) - Krour, Hichem; Tazi, Nacef; Trauchessec, Romain; Ben Fraj, Amor; Lecomte, André; Idir, Rachida; Barnes-Davin, Laury; Bolze, Breffni; Delhay, Arnaud
Abstract: The aim of this study is to improve the sustainability of cement and concrete mixes. To do so, the fine recycled aggregates (FRA) from construction and demolition wastes (CDW) were used in cement raw meals (CRM) to produce recycled clinker and cement to be used in the mix design of new concretes. About 7000 tons of clinker containing 1000 tons of FRA were generated at industrial scale, in a cement plant. Clinker was then incorporated into CEM I and CEM II recycled cements. The findings of this study confirm the feasibility of producing clinkers and cements with FRA, meeting the industry's required performance, and at the same time reducing resource depletion in the cement industry. These cements were also incorporated in new ordinary and high performance concretes. The results show slight differences in mechanical and durability properties, when recycled cements are used. From a performance approach viewpoint, the high performance concretes (conventional and recycled) are ranked as highly durable, while the ordinary concretes are ranked as low-medium durable ones, regardless the presence of FRA in cements. Graphical abstract: Image 1 Highlights: Incorporation of fine recycled aggregates to replace virgin materials in cement raw meal. Production of 7000 tons of clinker with fine recycled aggregates at industrial scale. Mechanical and durability investigation of C30 and C60 concretes with recycled cement. Ranking of investigated concretes using a performance approach.